2017
DOI: 10.1007/s11356-017-8542-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb, Zn, and Cd from contaminated soil by new washing agent from plant material

Abstract: Soil washing is an effective approach to remove soil heavy metals, and the washing agent is generally regarded as one of the primary factors in the process, but there is still a lack of efficient and eco-friendly agents for this technique. Here, we showed that four plant washing agents-from water extracts of Coriaria nepalensis (CN), Clematis brevicaudata (CB), Pistacia weinmannifolia (PW), and Ricinus communis (RC)-could be feasible agents for the removal of soil lead (Pb), zinc (Zn), and cadmium (Cd). The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…humic substances) (Kulikowska et al, 2015;Meng et al, 2017), biodegradable chelants (e.g. imminodisuccinic acid, methylglycinediacetic acid, citric acid and poly-γ-glutamic acid) (Begum et al, 2012;Guo et al, 2018), plant-derived washing agents (Cao et al, 2017a(Cao et al, , 2017b) and biosurfactants (Singh & Cameotra, 2013) have emerged as novel extractants in the soil washing process. To date, the applicability of these novel extractants has only been tested in the laboratory.…”
Section: Soil Washingmentioning
confidence: 99%
“…humic substances) (Kulikowska et al, 2015;Meng et al, 2017), biodegradable chelants (e.g. imminodisuccinic acid, methylglycinediacetic acid, citric acid and poly-γ-glutamic acid) (Begum et al, 2012;Guo et al, 2018), plant-derived washing agents (Cao et al, 2017a(Cao et al, , 2017b) and biosurfactants (Singh & Cameotra, 2013) have emerged as novel extractants in the soil washing process. To date, the applicability of these novel extractants has only been tested in the laboratory.…”
Section: Soil Washingmentioning
confidence: 99%
“…In addition, FTIR analysis was used to identify the functional groups of the soil. 57 Hydroxyl and carboxyl groups were proven to be important in the adsorption of heavy metals in soil. 58 In this study, the disappearance of carboxylic groups (1427 cm À1 ) and hydroxyl groups (1036 cm À1 ) illustrated the dissolution of organic matter aer washing (Fig.…”
Section: Surface Morphology Of Soil Particlesmentioning
confidence: 99%
“…Hong et al (2002), who used the Tessier fractionation procedure, found that saponin removed 83% of Cd from the exchangeable and carbonate fractions (equivalent to F1 fraction in the present study), and 33% of Cd from the Fe-Mn oxide fraction, but had little effect on the content of Cd in the organic fraction. Cao et al (2017) found that an aqueous extract from Coriaria nepalensis, Clematis brevicaudata, Pistacia weinmannifolia, and Ricinus communis plants at pH 4 was only able to decrease the Cd concentration in F1 fraction.…”
Section: The Effect Of Washing Agents From Sewage Sludge On CD Distrimentioning
confidence: 96%